Prevalence of Mental Disorders in Nepal: Findings from the Pilot Study - Jha, Anjani Kumar; Ojha, Saroj Prasad; Dahal, Sushma; Sharma, Pawan; Pant, Sagun Ballav; Labh, Sweta; Marahatta, Kedar; Shakya, Suraj; Adhikari, Ramesh Prasad; Joshi, Devrat; Luitel, Nagendra Prasad; Dhimal, Meghnath (Journal of Nepal Health Research Council, 2019)
Background: The global prevalence of mental disorders is high and has an increasing trend. In Nepal, there is dearth in literature on prevalence of mental disorders based on national representative sample. In this study, we aim to present the findings on the prevalence of mental disorders from the pilot study of National Mental Health Survey, Nepal. Methods: A cross-sectional study was conducted among 1647 participants aged 13 years and above in three districts of Nepal: Dhanusha, Bhaktapur and Dolakha each representing three ecological regions. Mini International Neuropsychiatric Interview (MINI) standard version 7.0.2 for DSM-5 was used for adults (aged 18 years and above), and kid version of the same tool was used for children (aged 13-17 years) in Nepali language. Separate sets of questions were added for epilepsy and dissociative conversion disorder that were not in the Mini International Neuropsychiatric Interview tool. Prevalence of assessed mental disorders was reported separately for adults and children.Results: The current prevalence of mental disorders among adults and children were 13.2% and 11.2% respectively. Substance use disorder, dissociative conversion disorder, major depressive disorder, alcohol use disorder and psychotic disorder were common among adults. Similarly, psychotic disorder, agoraphobia, major depressive disorder, and anxiety disorders were common among children. Current suicidality was present among 10.9% adults and 8.7% children.Conclusions: Our findings from the pilot study have given insight into the prevalence of different mental disorders in the survey areas. These findings can be utilized for planning the National Mental Health Survey, Nepal. Keywords: Mental disorders; mental health survey; MINI; Nepal; pilot study.